Engineering protonation conformation of l‐aspartate‐α‐decarboxylase to relieve mechanism‐based inactivation. Issue 6 (2nd March 2020) - Qian, Yuanyuan; Lu, Cui; Liu, Jia; Song, Wei; Chen, Xiulai; Luo, Qiuling; Liu, Liming; Wu, Jing
Abstract: Mechanism‐based inactivation of l ‐aspartate‐α‐decarboxylase (PanD), which leads to irreversible modification of active site, is a major challenge in the efficient production of β‐alanine from L ‐aspartic acid. In this study, a semi‐rational strategy that combined conformational dynamics and structural alignment was applied to increase the catalytic stability of Bacillus subtilis PanD ( BsPanD ). Using site‐saturation and C‐terminal deletion, the variant Q5 ( Bs PanD I46V/I88M/K104S/I126* ) was generated. The catalytic half‐life and the total turnover number (TTN) of Q5 were 3.48‐fold and 2.52‐fold higher, respectively, compared with that of the parent Q0. The reasons for the differences were the prolonged distance d1 between the phenolic group of Tyr58 and pyruvoyl group of Ser25 (4.9 Å in Q0 vs. 5.5 Å in Q5), an increased difficulty for incorrect protonation to occur, and the decreased flexibility of residues in regions A, B, and C, thereby enhancing the probability of correct protonation. Variant Q5, coupled with l ‐aspartase (AspA) in a 15‐L bioreactor, generated a linear cascade system using fumaric acid as a substrate, yielding 118.6 g/L β‐alanine with a product/catalyst (P/C) ratio of 5.9 g/g and a conversion > 99%. These results showed that reshaping the protonation conformation of PanD can efficiently relieve mechanism‐based inactivation and boost catalytic stability. Abstract : The mechanism‐based inactivation of l ‐aspartate‐α‐decarboxylase (PanD), which resulted in low catalytic stability, is a major challenge in the efficient production of β‐alanine by biotransformation. In this study, a combinational strategy of conformational dynamics and structural alignments were introduced to engineer Bs PanD protonation conformation for improving catalytic stability. Finally, 3.48‐fold increased catalytic half‐life and 2.52‐fold increased total turnover number (TTN) were obtained with the final variant Q5 compared with the parent Q0, which resulted in the highest product/catalyst (P/C) ratio reported so far.